PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN PROBLEM POSING DITINJAU DARI PENGETAHUAN AWAL TERHADAP PENGUASAAN KONSEP FISIKA SISWA SMK - Siti Nurdatul Jannah; Aris Doyan; Ahmad Harjono (Postgraduate, University of Mataram, 2016)
This study aims to determine the effect of cooperative learning through problem posing approach to the mastery of concepts of students in terms of prior knowledge. The method used is a quasi-experimental method with 2x2 factorial study design. The study population was 163 students of class XI SMKN 9 Mataram scattered in 5 classes. These samples included 55 students, divided into two classes by cluster of random sampling technique. The research instrument is a test mastery of concepts and problem solving skills test given at the beginning and end of the study. The data was analyzed by Manova two ways. The results showed that (1) students learn to use cooperative learning model with problem posing approach was significantly different in the aspect of mastery of concepts than students who study with learning cooperative model only, (2) students who have high prior knowledge different significantly in aspects of mastery of concept compared students who have low prior knowledge, (3) there was an interaction effect between learning model with prior knowledge of the mastery of concepts students. Keywors: Cooperative Learning Model, Problem Posing, Prior Knowledge, Concepts Mastery